The Effects of Internal Control Under International Standards Framework on Performance of Local Government in Chiang Mai Province - intakhan, tanapol; Chai-amonphaisal, Korravee (RMUTL Journal of Business Administration and Liberal Arts, 2022)
The purpose of this study was to examine the relationship between internal control under international standards framework and performance. The data were collected from 211 internal control officer of Local Government in Chiang Mai Province by using questionnaire. The 211 online questionnaires were replied by the respondents through Google Forms, represented 100.00 % of the respondents. The analysis of data used descriptive statistic, correlation analysis, and multiple regression analysis. The result of this research showed five components of internal control system consisting environment of the control, risk assessment, controlling activities, information and communication, and monitoring and evaluation. These five components had statistically significant relationship with performance. In addition, management support and information system were not moderating variables that were the relationship between internal control system and performance.